The gravity model of trade : a theoretical perspective - Shahriar, Saleh (Array, 2019)
Purpose. The purpose of this study is to trace the theoretical developments of the gravity model of trade. The key question is: what are the dominant features of the development of the gravity trade model? Methodology. This research is conducted by employing a number of methods that include the historical, descriptive and analytical methods. The main contribution of this paper is to trace the historical and theoretical development phases of the gravity model. Findings. This study is a novel attempt in terms of the identification of the four distinctive phases of the development of the gravity model. This work would, therefore, expand the existing literature on the gravity model. We argue that the development of the gravity model is the outcome of many research efforts. A large body of literature has given the model a solid theoretical foundation. But there is no consensus about the proper econometric estimation methods of the model. The gravity model is significant both historically and analytically. It is a useful tool for the analysis of international trade. It has become a popular research device used by the researchers and policy makers around the world. The gravity is regarded as one of the most successful models in the literature of international economics. Originality. The original contributions of this paper lie in streamlining the consistent historical development of the gravity model over a longer period of time-frame, ranging from 1885 to 2018. Limitations and Implications. This work is theoretical aspects of the trade gravity model. Future researchers could overcome the limitations by combining the theoretical and empirical studies in a paper. This paper can help the future researchers in dealing with the broad body of literature of gravity model. Acknowledement. This study was supported by the National Natural Science Foundation of China (grants No.71673223 & 71473197), and a PhD scholarship from the China Scholarship Council (CSC).